Surgical site infection after digestive surgery in a single tertiary hospital in Indonesia: six years of data (Medical Journal of Indonesia, 2020)
BACKGROUND Surgical site infection (SSI) is responsible for increasing cost, morbidity, and mortality related to surgical operations, and has continued to be a significant problem even in hospitals with advanced facilities. This study aimed to describe the SSI among patients after digestive surgery. METHODS From 2012 to 2017, all abdominal surgeries with SSI in Cipto Mangunkusumo Hospital, except obstetrics and gynecology cases, were included in the study. Demographic characteristics, nutritional status, preoperative and intraoperative conditions, wound contamination/SSI type, and mortality data were reported. RESULTS From 4,893 abdominal surgeries during the period, 135 subjects (2.8%) developed SSI with 42.2% of cases were the clean-contaminated type. Most of the cases were males (66.7%), aged between 2565 years old (80.0%), subjective goal assessment B (46.7%), had normal weight (57.8%), had longer duration of surgery (70.4%), and had preoperative stay between 215 days (65.2%). Most of the SSI patients survived (77.8%). CONCLUSIONS Even though the SSI in Cipto Mangunkusumo Hospital was low, it still needs improvement in preoperative care, intraoperative care, and SSI awareness. Therefore, further studies are required to understand how to reduce the incidence, risk, and SSI-related mortality.